Penerapan Computer Vision Menggunakan Metode Deep Learning pada Perspektif Generasi Ulul Albab - Arifin, Imamul; Haidi, Reydiko Fakhran; Dzalhaqi, Muhammad (Jurnal Teknologi Terpadu, 2021)
Machine learning is one of the applications of artificial intelligence. The use of machine learning in computer vision is closely related to deep learning where computer scientists get inspiration about deep learning technology from the environment. The purpose of the research in this manuscript is to know and understand deep learning technology along with simple examples in processing image objects and to know and understand artificial intelligence technology from the perspective of the ulul albab generation so that it can provide comprehensive benefits for the world. The research conducted in this paper is a type of qualitative research with library research using various books and other reading literature such as journals and special websites so as to produce information on the topic under study. Artificial intelligence technology will always develop and lead to increasingly sophisticated directions, but technology also has a negative impact. The Ulul Albab generation must be able to struggle to have a positive impact on society because the Ulul Albab generation is the hope for the progress of Islamic civilization in various sectors of science and technology.